13.625 Gb/s real‐time dual‐band adaptive optical orthogonal frequency division multiplexing transmissions over 25 km standard single‐mode fibre intensity modulation and direct detection systems utilising strongly saturated reflective semiconductor optical amplifier intensity modulators. Issue 5 (1st October 2014) - Zhang, Qianwu; Hugues‐Salas, Emilio; Giddings, Roger P.; Zhang, Junjie; Wang, Min; Tang, Jianming
Abstract : Record‐high 13.625 Gb/s real‐time end‐to‐end dual‐band optical orthogonal frequency division multiplexing (OFDM) transmissions are experimentally demonstrated over intensity modulation and direct detection‐based 25 km standard single‐mode fibres utilising 1.125 GHz reflective semiconductor optical amplifier (RSOA) intensity modulators. The 7.375 Gb/s OFDM baseband (0–2 GHz) and 6.25 Gb/s OFDM passband (4.125–8.125 GHz) are adaptively modulated independently and sampled at 4 GS/s. Experimental results show that strongly saturated RSOAs can intensity‐modulate adaptive bit‐ and power‐loaded radio frequency (RF) OFDM signals having bandwidths approximately eight times higher than the 3 dB small‐signal modulation bandwidths of the RSOAs.